In vitro Antimicrobial Activity of Chlorquinaldol against Microorganisms Responsible for Skin and Soft Tissue Infections: Comparative Evaluation with Gentamicin and Fusidic Acid - Bortolin, Monica; Bidossi, Alessandro; De Vecchi, Elena; Avveniente, Maura; Drago, Lorenzo (Frontiers in Microbiology, 2017)
Skin and soft tissue infections are a major therapeutic challenge for clinicians. The emergence of pathogens with decreased susceptibility to available therapies has become an emerging problem often associated with treatment failure. Hence, there is an urgent need for novel broad-spectrum antimicrobial agents. The purpose of this study was to assess the feasibility of chlorquinaldol as an alternative approach to currently used topical antibiotics for the treatment of skin and soft tissue infections. The activity of chlorquinaldol was investigated against a collection of bacterial isolates responsible for skin infections, including strains resistant to fusidic acid and gentamicin. After determination of MIC and MBC, time–kill experiments were carried out by counting colonies grown after 0, 3, 6, 9, 24 and 48 h of incubation with concentrations equal to ¼×, ½×, 1×, 2× and 4× MIC of chlorquinaldol, gentamicin or fusidic acid. Staphylococci resulted the most sensitive Gram-positives to chlorquinaldol, with MIC values ranging from 0.016 and 0.5 mg/L. A lower activity was observed against Gram-negative bacteria, with 77% of the isolates being inhibited at concentrations ranging from 128 to 512 mg/L. Generally, in time-kill studies, chlorquinaldol showed a bactericidal activity at the higher concentrations (2×, 4× MIC) after 24-48 h of incubation. In conclusion, chlorquinaldol may represent a valuable alternative to conventional topical antibiotics for the treatment of skin and soft tissue infections.